Anesthetic management of pediatric patients diagnosed with X‐linked adrenoleukodystrophy: A single‐center experience. Issue 2 (26th December 2019) - Kloesel, Benjamin; Dua, Nupur; Eskuri, Ryan; Hall, Jason; Cohen, Melissa; Richtsfeld, Martina; Belani, Kumar
Abstract: Background: X‐linked adrenoleukodystrophy is a progressive demyelinating disease that primarily affects males with an incidence of 1:20 000‐30 000. The disease has a wide spectrum of phenotypic expression and may include adrenal insufficiency, cerebral X‐linked adrenoleukodystrophy and adrenomyeloneuropathy. The condition has implications for the administration of anesthesia and reports of anesthetic management in those patients are limited at this point. Aim: To review the perioperative care, complications and outcomes of patients diagnosed with X‐linked adrenoleukodystrophy at the University of Minnesota Masonic Children's Hospital. Method: After obtaining IRB approval, we performed a retrospective chart review of pediatric patients diagnosed with X‐linked adrenoleukodystrophy who underwent either surgery or diagnostic/therapeutic procedures that included anesthesia services between January 2014 and December 2016. Data included demographics, American Society of Anesthesiologists classification, preoperative diagnosis, history of hematopoietic stem cell transplant, anesthetic approaches, airway management, medications used, intra‐ and postoperative complications, and patient disposition. Results: We identified 38 patients who had a total of 166 anesthetic encounters. The majority of patients underwent procedures in the sedation unit (75.9%) and received a total intravenous anesthetic with spontaneous ventilation via a natural airway (86.1%). Preoperative adrenal insufficiency was documented in 87.3% of the encounters. Stress‐dose steroids were administered in 70.5% of the performed anesthetics. A variety of anesthetic agents were successfully used including sevoflurane, isoflurane, propofol, midazolam, ketamine, and dexmedetomidine. There were few perioperative complications noted (6.6%) and the majority were of low severity. No anesthesia‐related mortality was observed. Conclusions: With the availability of skilled pediatric anesthesia care, children with X‐linked adrenoleukodystrophy can undergo procedures under anesthesia in sedation units and regular operating rooms with low overall anesthesia risk.